Evaluation of quality of clinical management of neuroendocrine tumors. Issue 4 (16th December 2022) - Bloemen, Hannah; Kneepkens, Kristien; Deraedt, Karen; Ivanova, Anna; Sergeant, Gregory; Mebis, Jeroen; Van der Speeten, Kurt
Abstract: Background: Neuroendocrine tumors (NETs) are a group of biologically and clinically heterogeneous neoplasms predominantly found in the gastrointestinal and bronchopulmonary tractus. Despite a rising incidence, implementation of evidence‐based standardized care for this heterogenous group remains challenging. The European Neuroendocrine Tumor Society regularly reviews guidelines regarding diagnostic and treatment strategies for NETs. The aim of this study is to shed light on the care of patients with a NET in Belgian Limburg, to provide data as a basis for future studies and to check whether data and results are according to consensus guidelines and outcomes described in literature. Methods: Our study concerned a detailed observational data collection of two large Belgian hospitals (Jessa Hospital Hasselt and Hospital Oost‐Limburg Genk) with special interest in patient profile, quality of pathology reports, use of diagnostic imaging, and overall survival. Data on 188 patients were assembled between January 2010 and December 2014 with follow‐up until June 2016 (median follow‐up: 33.6 months). Results: Fifty percent of patients were male. NETs were located mainly in the digestive tract (63.8%) and lung (20.2%). Appendiceal NETs were diagnosed at a significantly younger age than other tumors (41.3 vs. 64.0 years). Overall, a mean pathology report quality score of 3.0/5 was observed with the highest scores for small bowel NETs. Diagnostic and nuclear imaging was performed in 74.5% and 29.8% of cases, respectively. Seventy‐four percent of the population survived until the end of the observation period with highest survival rates for appendiceal and small bowel NETs. Conclusion: Overall, epidemiological results were comparable with findings in the literature. Gastrointestinal NETs met most of the requirements of qualitative pathology reporting and diagnostic imaging as listed in the European Neuroendocrine Tumor Society consensus guidelines. However, consensus with regard to bronchopulmonary NETs is still scarce and remains an objective for future research. Moreover, discussing treatment strategies in specialized multidisciplinary tumor boards would facilitate regional care. Abstract : Overall, the epidemiological results of our neuroendocrine tumor (NET) cohort were comparable with findings in literature. Gastrointestinal NETs met most of the requirements of qualitative pathology reporting and diagnostic imaging as listed in the European Neuroendocrine Tumor Society consensus guidelines. Discussing treatment strategies in specialized multidisciplinary tumor boards would facilitate regional care.